3-Hydroxy-5,6-epoxy-β-ionone Isolated from Invasive Harmful Brown Seaweed Sargassum Horneri Protects MH-S Mouse Lung Cells from Urban Particulate Matter-Induced Inflammation - K. K. Asanka Sanjeewa (MDPI AG, 2021)
Air pollution is a process that mixes pollutants into the atmosphere, which is potentially harmful to humans and causes negative impacts on the surrounding environment (biotic and abiotic). The negative health effects associated with air pollution have been reported from both indoor and outdoor environments. Specifically, dust storms originating in Chinese and Mongolian desert areas introduce significant amounts of particulate matter (PM) to the Korean atmosphere. Previously, several studies reported that urban PM (UPM) is a potential agent that causes inflammation in the lungs by altering multiple signal transduction pathways; therefore, screening and identification of anti-inflammatory compounds against UPM-induced inflammation is an urgent requirement. In the present study, we attempted to study the anti-inflammatory properties of 3-Hydroxy-5,6-epoxy-β-ionone (HEBI), a pure compound isolated from invasive brown seaweed, Sargassum horneri (brown edible seaweed), against UPM-stimulated lung macrophages (MH-S). Anti-inflammatory parameters of HEBI were evaluated using Western blots, ELISA, RT-qPCR, and MTT assays. According to the results, HEBI at concentrations between 31.3 and 125 µg/mL reduced UPM-induced NO, PGE2, and pro-inflammatory cytokine production via blocking the downstream signal transduction of NF-κB and MAPKs. Specifically, HEBI down-regulated the mRNA expression levels of Toll-like receptors 2 and 4, which are well-known NF-κB and MAPKs stimulators. Taken together, HEBI is a potential candidate to develop functional foods and active ingredients in cosmeceuticals because of its profound effects against UPM-induced inflammation in MH-S macrophages.